1987
DOI: 10.1289/ehp.8773247
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of parasitic infection for the behavior of the mammalian host.

Abstract: As many as one billion people may be infected with animal parasites. The behavioral consequences of such infection, or of illness in general, is poorly understood. This issue is discussed using as an example infection of mice with Toxocara canis, the common roundworm of dogs. Current literature suggests that two-thirds of all dogs have been infected with this parasite, and 7% of all humans have antibodies to T. canis. T. canis completes its life cycle in dogs, but when it infects aberrant mammalian hosts (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
1
6
0
1
Order By: Relevance
“…A similar situation could be proposed for the relationship between T. canis larvae, rodents and dogs and some authors have actually verified the occurrence of behavioral alterations in mice infected by larvae of this ascarid 2,6,7,8,9,10 , though not as clearly as has been demonstrated for the interaction between Toxoplasma gondii and rodents. Moreover, the great majority of papers on this issue used mice and not Rattus norvegicus.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A similar situation could be proposed for the relationship between T. canis larvae, rodents and dogs and some authors have actually verified the occurrence of behavioral alterations in mice infected by larvae of this ascarid 2,6,7,8,9,10 , though not as clearly as has been demonstrated for the interaction between Toxoplasma gondii and rodents. Moreover, the great majority of papers on this issue used mice and not Rattus norvegicus.…”
Section: Discussionsupporting
confidence: 56%
“…Some authors have reported behavioral alterations and learning impairment in mice infected by T. canis larvae 2,6,7,8,9,10 . Recently, one study reported diminished muscular strength in R. norvegicus experimentally infected by T. canis larvae, suggesting some enhancement of the preypredation mechanisms of infection 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Parasitic infections can also alter sleep patterns, due to the resulting immune response or through direct effects. Because parasites are multicellular organisms, they can modify certain behaviors to facilitate infection and complete their life cycle [ 89 ]. It is possible that sleep is a state in which they can exploit the infected host, because the responsiveness to external stimuli declines, rendering the host more susceptible to infection.…”
Section: Parasitic Infections and Sleepmentioning
confidence: 99%
“…Acute and chronic sleep deprivation modifies the immune response, and conversely, immunological challenges modify the normal sleep pattern. They may be able to modify certain behaviours to facilitate infection and complete their life cycles 38 . However, this field still remains poorly studied, and consequently the function of sleep in the immune response to pathogens beginning to be understood.…”
Section: Discussionmentioning
confidence: 99%